Ratiometric and Colorimetric Optical Thermometers Using Emissive Dimeric and Trimeric {[Au(SCN)2]−}n Moieties Generated in d–f Heterometallic Assemblies. (16th March 2022) - Kumar, Kunal; Stefanczyk, Olaf; Chorazy, Szymon; Nakabayashi, Koji; Ohkoshi, Shin‐ichi
Abstract: Gold complexes can generate excimers ([Au2 ]→[Au2 ]*) and exciplexes ([Au3 ]→[Au3 ]*) with light excitation. Four Gd III and Y III complexes were assembled with dimeric {[Au(SCN)2 ] − }2 and trimeric {[Au(SCN)2 ] − }3 bis(thiocyanato)gold(I) counterions. The vibrational signature associated with the Au⋅⋅⋅Au vibrational mode was probed with ultralow frequency (ULF) Raman spectroscopy as a function of temperature. Emission spectroscopy was used to explore photophysical properties. Two broad features in the high‐ and low‐energy regions were associated with the fluorescence and phosphorescence of the gold entities, respectively. Temperature‐dependent luminescence measurements showed that the emission color can be tuned from blue to green via cyan and white. Hence, these complexes can act as colorimetric thermometers. Additionally, a ratiometric thermal sensing ability was incorporated with high sensitivity up to 5 % K −1 in the cryogenic temperature range. Abstract : The {[Au I (SCN)2 ] − }2 and {[Au I (SCN)2 ] − }3 ions were incorporated in two different supramolecular matrices with Gd III and Y III . The resulting materials exhibit characteristic Au⋅⋅⋅Au vibrational peaks investigated by ultralow frequency Raman spectroscopy and DFT calculations. The formation of Au2 and Au3 moieties yields strong photoluminescence with rich color tunability, providing high‐performance colorimetric and ratiometric thermometer abilities.